Association Between Glaucoma, Glaucoma Therapies, and Erectile Dysfunction. Issue 2 (February 2015) - Nathoo, Nawaaz A.; Etminan, Mahyar; Mikelberg, Frederick S.
<x xml:space="preserve">Abstract</x> Purpose: To examine the association between (1) glaucoma and erectile dysfunction (ED) and (2) topical β-blocker (BB) use and ED. Methods: A comprehensive, province-wide database of physician visits and diagnoses and prescription drug dispensing was used to identify cases of ED (1380) and find corresponding controls (13, 800). A conditional logistic regression model was used to estimate rate ratios for 2 main exposures: (1) diagnosis of glaucoma and (2) use of a prescription of a topical BB before the index date. A variety of risk factors were adjusted for. Results: Cases were more likely to have coronary artery disease, chronic obstructive pulmonary disease, and diabetes. A crude rate ratio of the current diagnosis of ED in a population with at least 2 separate diagnoses of glaucoma was 1.34 and when adjusted for a number of variables (including oral BB use), this ratio was 1.37 [95% confidence interval (CI), 1.06-1.76]. Use of topical BB in the 30 days before the diagnosis of ED did not have a significant association with a diagnosis of ED, with crude and adjusted rate ratios of 1.05 and 1.10, respectively (95% CI, 0.61-1.99). Topical ocular prostaglandin use was also not associated with ED, with crude and adjusted rate ratios of 0.96 and 0.93, respectively (95% CI, 0.57-1.53). Conclusions: Our results confirmed an association between ED and glaucoma that cannot be attributed to topical BB use. Given that most cardiovascular and metabolic risk factors were adjusted for, further research in this area will be necessary to elucidate the nature of this association and potential causation.